PARP1 V762A polymorphism affects the prognosis of myelodysplastic syndromes. (4th March 2020) - Gotoh, Nanami; Minato, Yusuke; Saitoh, Takayuki; Takahashi, Noriyuki; Kasamatsu, Tetsuhiro; Souma, Kana; Oda, Tsukasa; Hoshino, Takumi; Sakura, Toru; Ishizaki, Takuma; Shimizu, Hiroaki; Takizawa, Makiko; et al.
Abstract: Objective: Myelodysplastic syndromes (MDS), caused by various genetic mutations in hematopoietic stem cells, are associated with highly variable outcomes. Poly (ADP‐ribose) polymerase‐1 (PARP1) plays an important role in DNA damage repair and contributes to the progression of several types of cancer. Here, we investigated the impact of PARP1 V762A polymorphism on the susceptibility to and prognosis of MDS. Methods: Samples collected from 105 MDS patients and 202 race‐matched healthy controls were subjected to polymerase chain reaction‐restriction fragment length polymorphism for genotyping. Results: The allele and genotype frequencies of PARP1 V762A did not differ between MDS patients and the control group. However, MDS patients with the PARP1 V762A non‐AA genotype, which is associated with high gene activity, had shorter overall survival rates ( P  = .01) than those with the AA genotype. Multivariate analysis of overall survival also revealed PARP1 V762A non‐AA genotype as a poor prognostic factor ( P  = .02). When patients were analyzed according to treatment history, the PARP1 V762A non‐AA genotype was only associated with poor survival in patients who had received treatment ( P  = .02). Conclusion: PARP1 V762A polymorphism may be an independent prognostic factor for MDS, and a predictive biomarker for MDS treatment.